2015
DOI: 10.1186/s12889-015-1434-x
|View full text |Cite
|
Sign up to set email alerts
|

Parental risk perceptions of child exposure to tobacco smoke

Abstract: BackgroundTobacco smoke exposure harms children and adults. Yet, 40% of children worldwide are exposed to tobacco smoke in their homes. Such widespread parental failure to protect children is puzzling, and may be related to risk perceptions. No consensus exists about how to measure parental risk perceptions of tobacco smoke exposure.MethodsThe objective of this research was to study Parental Risk Perceptions of child Exposure to Tobacco Smoke (PRETS) using various dimensions of risk perceptions: likelihood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 28 publications
3
34
0
3
Order By: Relevance
“…Without exception, all of these studies used measures of “concern” or “worry” regarding a risk. Seven studies (9%) measured risk perception following the traditionally accepted definition of risk, including separate items to measure probability & consequences (e.g., Matthew et al., ; Rosen & Kostjukovsky, ; Yang, ). Probability was assessed with one or more items asking about the “chances,” “likelihood,” or “probability” of realizing a risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Without exception, all of these studies used measures of “concern” or “worry” regarding a risk. Seven studies (9%) measured risk perception following the traditionally accepted definition of risk, including separate items to measure probability & consequences (e.g., Matthew et al., ; Rosen & Kostjukovsky, ; Yang, ). Probability was assessed with one or more items asking about the “chances,” “likelihood,” or “probability” of realizing a risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study found that beliefs about third-hand smoke are associated with home smoking rules [50]. Parental risk perceptions have been shown to be associated with smoking behavior in homes with children in some studies but not others [51]. Unsurprisingly, heavier smoking is known to be associated with higher exposure of children [52].…”
Section: Possible Reasons For Continued Child Exposure and The Potenmentioning
confidence: 98%
“…Kekosongan wacana tentang stunting maupun balita pendek saat iniyang masih terbatas pada aspek fisik sematadapat menyebabkan ibu-ibu mengabaikan dalam memantau tinggi badan anak balita. Penelitian menyimpulkan adanya korelasi yang konsisten antara perilaku kesehatan dengan persepsi terhadap adanya ancaman penyakit sehingga persepsi risiko menjadi salah satu konsep kunci dalam memprediksi perilaku kesehatan keluarga (L. Rosen & Kostjukovsky, 2015) maupun masyarakat (Brewer et al, 2007). Sementara pengetahuan menjadi faktor berpengaruh dalam membentuk persepsi (Slovic, 1986), maka penggunaan saluran komunikasi yang efektif dapat menambah pengetahuan dan menjangkau kelompok target menjadi salah satu tulang punggung untuk mendidik masyarakat menghindari hal-hal yang tidak diinginkan (Boyd & Furgal, 2018;L.…”
Section: Pandanganunclassified